Brandscapes: contrasting corporate-generated versus consumer-generated media in the creation of brand meaning. Issue 3 (5th May 2015) - Shao, Wei; Jones, Richard Gyrd; Grace, Debra
Abstract : Purpose: – The purpose of this paper is to add to the growing literature addressing whether, and to what extent, brand meaning is determined by corporate and consumer-generated processes. To do this, the authors compared the expression of brand meaning across three key sources i.e. first, brand strategy (i.e. traditional marketing mix); second, corporate-generated media (i.e. web site); and third, consumer-generated media (Facebook). Design/methodology/approach: – To address the research question of this study, the authors conducted an in-depth investigation into consumer co-creation experiences in the context of Facebook brand communities. The authors then interpreted the findings in relation to the brand strategy (i.e. marketing mix) and brand meaning expressed via corporate-generated online media (i.e. corporate web site). The authors achieved this by applying a narrative discourse analysis to textual data. To effectively handle the high quantity of textual data spawned via consumer-generated media (i.e. Facebook), the authors used a computer-assisted content analysis application (i.e. Leximancer). Findings: – In the analyses the authors found that brand expressions varied considerably across the chosen retail brands, but in all cases strong integration and alignment were present between the corporate and consumer-generated media. Specifically, the authors found that Facebook interactions echoed the brand meanings espoused on the corporate web sites. The findings indicate that online marketers can define the nature of brand co-creation, especially in the context of Facebook interactions. Practical implications: – For marketers who are eager to take advantage of Web 2.0 to build their brand, the findings of this research are highly significant. The authors showed that the brands developed their own interaction profiles, which allowed them to align the Facebook content with their core brand values. The results indicate that sound brand governance is articulated through the effective management of social media touchpoints by providing interactive, content rich, and relevant Facebook sites that echo core brand values. Originality/value: – Even though businesses have now started to penetrate the online social networks and offer direct links from corporate web sites to social networking sites like Facebook and Twitter, little is known regarding the relationship between social media and traditional media in brand building. This research addresses this gap by undertaking an exploratory study of Facebook brand communities with implications for brand co-creation and brand governance.